Islamophobia in the film bulan terbelah di langit amerika: An islamic education perspective - Mowafg Abrahem Masuwd; Natasya Putri; Sigit Tri Utomo; Ana Sofiyatul Azizah (Yayasan Azhar Amanaa Yogyakarta, 2025)
Islamophobia is an irrational dislike or fear and a bad prejudice against Muslims or Islam. Indonesian Cinema launched one of the films entitled Bulan Terbelah di Langit Amerika. This film shows the treatment of American society that demeans Islam and the attitude of anti-pluralism towards other teachings. The purpose of this research is to find out the dimensions of the phenomenon of Islamophobia in the film Bulan Terbelah di Langit Amerika, to find out the Islamophobia in the film Bulan Terbelah di Langit Amerika from the perspective of Islamic education, and to find out the relevance of the film Bulan Terbelah di Langit Amerika with the value of Islamic education. This research uses a semiotics approach, with the type of literature study research, using qualitative research methods, with primary data sources of the phenomenon of Islamophobia in the film Bulan Terbelah di Langit Amerika and secondary data sources from journals, articles, novels related to the research. The data collection technique uses the observation-note technique, the analysis technique uses content analysis, and the validity of the data uses reference materials. In this study, the phenomenon of Islamophobia, the dimension of private Islamophobia and the dialectic of Islamophobia were found.The film Bulan Terbelah di Sky America is very relevant to Islamic education, namely the values of khuluqiyah and amaliyah.